(untitled) (Journal of the College of Languages (JCL), 2024)
The article analyzes the neologisms that arose in the Iraqi dialect after the 2003 US-British invasion and the fall of Saddam Hussein’s regime, according to the theory I advocate: "The Basic Outline of Reference," a developed theory of Arab legacy and cognitive theory, which came out in 1987 in America, so we have used the terminology of cognitive grammar. In this theory it is stated that the reference is the interaction between four components: perception, imagination, imaginative comprehension and the linguistic sign or symbolization (the neological word in this article), which are closely related, so that none of them can be lacking, because they constitute a holistic whole that belongs to a deeper level. Let us see how the speakers of Iraq, after the invasion of 2003, imagine the world according to their views, that is, their collective imaginative comprehension. This theory is going to be in the future the basis of a modern holistic linguistics which is very different from traditional linguistics. Resumen El articulo analiza los neologismos surgidos en el dialecto iraquí tras la invasión estadounidense-británica de 2003 y la caída del régimen de Saddam Hussein, Desde la perspectiva de “El esquema básico de la referencia”, teoría que aúna el legado de la tradición lingüística árabe y la teoría cognitiva desarrollada a partir de los primeros años 80 en EEUU, por ello que adoptemos la terminología de la gramática cognitiva. En esta teoría se considera que la referencia es la interacción entre cuatro componentes: la percepción, la imaginación, la comprensión imaginativa y el signo lingüístico o simbolización (la palabra neológica en este artículo), que están íntimamente relacionados, de manera que no puede faltar ninguno de ellos, porque constituyen un todo holístico que pertenece a otro nivel más profundo. Vamos a ver como los hablantes de Irak, tras la invasión de 2003, imaginan el mundo según sus puntos de vista, es decir, su comprensión imaginativa colectiva. Esta teoría pretende fundamentar las bases de una lingüística holística diferente de la tradicional lingüística. Received on 2/6/2023 Accepted on 20/8/2023 Published on 2/1/2024